2022
DOI: 10.1002/app.53103
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of waterborne polyimide‐modified epoxy resin with high thermal properties and adhesion properties

Abstract: In response to the theme of environmental protection and green development in the world in the recent years, waterborne epoxy resin has received more and more attention. Waterborne epoxy resin has lower toxicity, but its low toughness limits the application range of waterborne epoxy resin. Here, we first proposed a method of toughening waterborne epoxy resin with aqueous polyamide salt solution. In this article, a series of waterborne polyamic acid salts is used as modification polymer to improve the high‐temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Moreover, if the majority of amide groups on the PAA chain are cured with EP at a relatively low temperature, then there are fewer amide groups left for imidization to form PI, and the expected superior thermally stable PI-EP copolymer matrix will not be obtained. Previous studies [ 17 , 18 , 19 , 20 , 27 , 28 , 29 , 30 ] reported that the PI-EP copolymer matrix could be obtained as expected, and benefits from both PI and EP have been observed. There must be some critical points worth noticing in the process of copolymerization.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, if the majority of amide groups on the PAA chain are cured with EP at a relatively low temperature, then there are fewer amide groups left for imidization to form PI, and the expected superior thermally stable PI-EP copolymer matrix will not be obtained. Previous studies [ 17 , 18 , 19 , 20 , 27 , 28 , 29 , 30 ] reported that the PI-EP copolymer matrix could be obtained as expected, and benefits from both PI and EP have been observed. There must be some critical points worth noticing in the process of copolymerization.…”
Section: Introductionsupporting
confidence: 62%
“…Using PAA with different terminal functional groups could be a feasible way [ 26 ]. Xing et al and others [ 27 , 28 ] used waterborne PI to modified waterborne EP resin by neutralizing the precursor (PAA) with 2-methylimidazol for PAA salt (PAAS) formation, after which the salt is basically waterborne. Accordingly, they found the copolymerized PAAS and EP copolymer with a semi-interpenetrating structure.…”
Section: Introductionmentioning
confidence: 99%
“…The first challenge is the selection of modifiers with specific structural units. Normally, introducing modifiers with only flexible structures into EPs is beneficial to dissipate stress, while they tend to form loose networks, making it difficult to construct a cross-linked network that couples hardness with softness and overcomes the strength–toughness trade-off. Therefore, it is necessary to introduce rigid and flexible structures that can work synergistically into EPs. The second challenge is the establishment of a relationship among modifiers, network topology, and properties.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solvent-based resins containing volatile organic compounds (VOCs) and other potential pollutants have been restricted by the progressively tighter government regulations in spite of their superior performance . Waterborne resins in which organic solvents are replaced with water to minimize the solvent content and unfavorable odor are an economical and environmentally friendly alternative. , Although waterborne resins have been widely studied, the performance of most water-based coatings are not as good as that of the solvent-based counterparts, partly due to the limited types and restricted molar mass of resins that can be stably emulsified in water . Waterborne resins that can fulfill all kinds of requirements and perform as well as, or even better than, the solvent-based resins remain a class of materials under development in academia and industry. , …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Although waterborne resins have been widely studied, the performance of most water-based coatings are not as good as that of the solvent-based counterparts, partly due to the limited types and restricted molar mass of resins that can be stably emulsified in water. 21 Waterborne resins that can fulfill all kinds of requirements and perform as well as, or even better than, the solvent-based resins remain a class of materials under development in academia and industry. 15,22−34 Regarding the preparation of waterborne epoxy/acrylic resins, there have been two main strategies.…”
Section: Introductionmentioning
confidence: 99%